PENINGKATAN KESEJAHTERAAN PEREKONOMIAN MASYARAKAT MELALUI LABELISASI BER-BAHASA INGGRIS - Ardini, Sukma Nur; Kustantinah, Indri; Suwandi, Suwandi; K.A., A.B. Prabowo (Fakultas Sains dan Teknik, Universitas Bangka Belitung, 2024)
Blimbing Village, Boja District, Kendal Regency is a tourist village where most of the population own small and medium micro enterprises (UMKM), one of which is fermented sticky rice (tape ketan) UMKM. Tape Ketan is a unique traditional Indonesian food that should be developed and introduced more widely nationally and internationally because of its various benefits. Based on the observations made by the PKM team, Tape Ketan producers face obstacles, namely the need for widespread product marketing and limited business capital. From these obstacles, the PKM team from the English Education Study Program UPGRIS provided a solution employing unique and creative product labeling in English so that sticky rice tape products are known to the public internationally. Creating brands, labeling and packaging products in English, and exploring the benefits and efficacy of products are the primary materials for the team, which is carried out in three stages: training, mentoring, and evaluation. The result obtained after going through these stages is a label design that has a brand and has been realized in packaging tape products. All product labeling is in English. The work results were evaluated, and the feedback from the practitioner was excellent in terms of term usage, wording, and product descriptions.